A model for the carbon fiber breakage along the twin‐screw extruder. (29th April 2021) - Malatyali, Hatice; Schöppner, Volker; Rabeneck, Nils; Hanselle, Felix; Austermeier, Laura; Karch, David
Abstract: Carbon fiber‐reinforced plastics (CFRP) are widely used in the plastics industry. The production of CFRP is mostly carried out on the twin‐screw extruder. Many different process variables change the process ability and the final fiber length in the product. In the literature, some models for fiber length decrease along the extruder with glass fibers can be found. The effects of the processing conditions on the final length for glass fiber are determined. In comparison, the incorporation behavior of the carbon fibers are not sufficiently analyzed. The purpose of this paper is to predict the fiber breakage along the screw for carbon fibers. First of all, the buckling case must be determined. The basis of the modeling is a fragmentation equation, for which a break probability and a break rate are defined. A comparison with experimental data shows satisfactory results. Abstract : The fiber length calculation starts with the definiton of the fiber and the polymer properties in SIGMA (Simulation program for twin screw extruder). After the process calculation in SIGMA, the local residence time, viscosity and shear rate can be extracted. With the inflated shear rate for fibers and the extracted values, the calculation in MATLAB® starts. After the end time is reached, a fiber length decrease along the screw is plotted in a diagram.